PERBANDINGAN PELAKSANAAN STANDING STORK TEST SECARA DARING DAN TATAP MUKA BAGI SISWA SEKOLAH MENENGAH PERTAMA NEGERI 1 BANGKALAN - Putri, Melly Nur Aulia; Hidayatullah, Fajar; Himawan, Agus; Anwar, Khoirul (Universitas Negeri Surabaya, 2021)
This research is a research that uses a standing stork test instrument where the implementation will be carried out online and offline with students of UPTD SMP Negeri 1 Bangkalan. This study was conducted to compare the results of the standing stork test conducted online and face-to-face. The impact of COVID-19 in the world of education is still being felt today. The learning system used will continue to be adapted to the spread of COVID-19 in their respective areas. Blended learning combines offline and online learning which increases the effectiveness of exploring the potential of students. This study uses comparative research with a quantitative approach. Online data collection techniques using video conferencing (zoom meeting, google meet, etc.). Meanwhile, face-to-face data collection techniques are carried out in the school field while still applying health protocol standards. Paired t-test was used to analyze the data and the results showed that there was no significant difference between the online and offline test instruments.